An Evidence-Informed Framework to Promote Mental Wellbeing in Elite Sport - Purcell, Rosemary; Pilkington, Vita; Carberry, Serena; Reid, David; Gwyther, Kate; Hall, Kate; Deacon, Adam; Manon, Ranjit; Walton, Courtney C.; Rice, Simon (Frontiers in Psychology, 2022)
Elite athletes, coaches and high-performance staff are exposed to a range of stressors that have been shown to increase their susceptibility to experiencing mental ill-health. Despite this, athletes may be less inclined than the general population to seek support for their mental health due to stigma, perceptions of limited psychological safety within sport to disclose mental health difficulties (e.g., selection concerns) and/or fears of help-seeking signifying weakness in the context of high performance sport. Guidance on the best ways to promote mental health within sporting environments is increasing, though current frameworks and position statements require greater focus on a whole of system approach, in which the needs of athlete, coaches and high-performance staff are considered within the context of the broader ecological system in which they operate and perform. This paper synthesises existing research, reviewed for translatability by mental health professionals working in elite sport, to provide an evidence-informed framework with real world utility to promote mentally healthy environments for all stakeholders in elite sporting organisations, from athletes through to administrators. Recommendations are provided to positively impact the mental wellbeing of athletes and support staff, which may in turn influence athletic performance. This framework is intended to provide sporting organisations with evidence-informed or best practice principles on which they can develop or progress their policies to support mental health promotion and prevent the onset of mental health difficulties. It is intended that the framework can be adapted or tailored by elite sporting organisations based upon their unique cultural, contextual and resourcing circumstances.